„Mój dom moją twierdzą”. Rozważania na tle regulacji art. 25 § 2a k.k. - Kania, Agnieszka (Wydawnictwo Uniwersytetu Wrocławskiego, 2018)
The purpose of the article is to discuss the latest change that has been introduced into the legislation regulating the right of necessary self-defence. The result of the said amendment is adding a new editing unit to the content of article 25 of the Penal Code, i.e. § 2a, which provides for impunity of a person excessively exercising the right of necessary self-defence in a situation where crossing the limits of necessary self-defence occurs when countering an attack involving forced entry into a flat, premises, house or an adjacent fenced area, or where crossing the limits of necessary self-defence occurs when countering an attack preceded by forced entry into these places. This study presents not only arguments of the drafters which they used to prove the validity of the analysed solution, but also points out some doubts that might occur in the practical application of this regulation.
Keywords: samoobrona konieczna; granice niezbędnej samoobrony; wykroczenie domowe